An Intervention Programme to Facilitate the Preschool Transition in Mexico - Urbina-Garcia, Angel (Frontiers in Education, 2020)
Over the last two decades there has been a growing interest in promoting a smooth transition to the first grade of primary school, given the potential long-term change this can have in preschool children at an academic and personal level. Research shows that psycho-educational interventions help improve children’s academic and personal skills, lessening the effects of this challenging period. The effectiveness of transition-related interventions has been mainly focused on developed economies, such as Australia, the US, the UK, Italy, Hong Kong, etc. However, there is limited evidence regarding how this type of intervention could support stakeholders in developing economies, such as Latin America. The Latin American region displays some of the lowest rates of academic performance and highest rates of social inequality in the world, making this region a priority in the international research agenda. This study sought to explore the efficacy of an intervention programme to facilitate this transition in Mexico City. Findings provide evidence of the positive impact of the preschool transition-intervention programme on children’s cognitive, social and fine motor skills, as well as in the frequency with which preschool teachers (PT) and the teaching assistants (TA) use transition practices that promote literacy in preparation for the first grade of primary school. Parents reported that the quality and closeness of the primary school were the main factors to consider when choosing the primary school that their child will attend. Parents reported that promoting academic skills in their child is essential to prepare them for this transition. Implications for policy and practice are discussed.